AN ANALYSIS OF ARTICLES ON NHT STRATEGY IN COMPREHENDING NARRATIVE TEXT FOR SMP-MTS IN INDONESIA - Dwitya Aprilia; Syofia Delfi; Maria Syafrianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This research was aimed to find out how the use of Numbered HeadsTogether Strategy (NHT) Numbered Heads Together Strategy (NHT) in seven studiescan improve/effect on the students’ reading comprehension. This research was libraryresearch by scollecting seven journalson the use of NHT strategy for junior high schoolstudents in comprehending narrative texts as the sources of data. The data wereanalyzed by implementing Descriptive Analysis and Content Analysis. The result of dataanalysis showed that implementing NHT could improve students’ readingcomprehension. It was as shown in the finding of this study in which the use of NHT incomprehending narrative texts for Junior High School students was constructive interms of the stages and inspiring in terms of the students’ ability in comprehendingnarrative texts. Based on the result of this study, it is expected that it can be used asbasic information or reference to conduct other researches because Numbered HeadsTogether provides more opportunities for students to help each other in mastering thematerial and to actively engage them in solving the problems. It is also suggested forfurther researchers to apply Numbered Heads Together for other skills and other kindgenres of texts.Key Words: Numbered Heads Together, Reading Comprehension,Narrative Text, Analysis